Nilai Moral Figur Putri Mandalika dalam Profesi Akuntan - Putri Fitri Ajiani, Ika; Hamidah, Hamidah (E-Jurnal Akuntansi; Vol 30 No 4 (2020), 2020)
This study departs from the legendary story of Princess Mandalika which is the basis for the moral values of the figure of the Princess Mandalika seen in the accounting profession, especially women. The moral value consists of the value of sacrifice and the value of emancipation. This research uses a phenomenological approach. Data collection techniques using semi-structured interview techniques. The informants who are the object of research are the Culture and Professional Practitioners of Accountants. The results of this study indicate that the value of sacrifice and the value of the emancipation of the figure of Princess Mandalika are still alive in the accounting profession, especially women. Keywords: Sacrifice Value; Emancipation Value; Putri Mandalika; Professional Accountant.